Analysis of Factors Influencing Pregnant Women in the Completeness of Antenatal Care Visits at UPTD Puskesmas Care Kutambaru, Lawe Bulan District, Southeast Aceh Regency - Selian, Susi Fitri; Effendy, Ismail; Nasution, Ramadhani Syafitri (PROMOTOR, 2025)
ANC or anteatal care is the care of the mother and fetus during pregnancy. Currently, the proportion of maternal mortality is approximately 305 deaths per 100 thousand live births, where the largest deaths occur in hospitals, around 77% of mothers cannot be saved, one of which is because the mothers who are referred to the hospital are already in a condition of severe complications. The purpose of this study is to analyze pregnant women in the completeness of antenatal care visits in the Working Area of the Kutambaru Care Health Center, Lawe Bulan District, Southeast Aceh Regency. This type of research uses a mixed method. The population in this study was 112 respondents, the sample in the study was 53 respondents with a slovin formula with a random sampling technique for qualitative using 9 informants. The variable results entered the multivariate test because the P value was ≤ 0.25. The results of the Multivariate analysis showed significant values and the variables of Exp(B) were, Knowledge (0.015) Exp(B) (3.572), Education (0.001) Exp(B) (0.007), Attitude (0.018) Exp(B) (1.398), Parity (0.009) Exp(B) (1,786), Income (0.000) Exp(B) (0.008), Distance (0.001) Exp(B) (1,904), Maternal Health (0.005) Exp(B) (1,556), Health Worker Support (0.001) Exp(B) (2,387). Results of Qualitative Data Analysis with Data Reduction, Data Display and Conclusion Drawing/Verification.From the results of in-depth interviews, it was found that there was an influence on the completeness of the ANC visit with factors of knowledge, education, attitude, parity, income, distance, maternal health and support of health workers. The conclusion of this study is that there is a relationship between knowledge, education, attitude, parity, income, distance, maternal health and health worker support for the completeness of ANC visits, the knowledge factor is the most dominant influencing ANC examination in pregnant women with an Exp(B) value of 3.572. It is hoped that health workers at the Kutambaru Health Center will be more routine in delivering health education to pregnant women about the importance of ANC examinations.